Pemberdayaan Siswa melalui Program Edukasi Kenakalan Remaja untuk Menciptakan Generasi Beretika - Agusty, Rizal Ubaidil Bar; Khodir, Qundhori Abdul; Dhiyaa A, Muhammad; Kurnia, Afifah Dwi; Rosidah, Dinda; Amatullah, Afifa Afra (Welfare : Jurnal Pengabdian Masyarakat, 2025)
Juvenile delinquency is a social problem that has an impact on adolescent development. This research aims to evaluate the effectiveness of socialization programs in increasing students' awareness of the prevention of juvenile delinquency. The method used is service learning with stages of investigation, preparation, action and reflection. Activities were carried out at SMPN 4 Malang through lectures, interactive discussions and educational video screenings. The results show an increase in students' understanding based on a comparison of pre-test scores (67.58) and post-test (77.58), with a difference of 10 points. The statistical test shows a significance value of 0.008 (<0.05), which indicates a significant increase in student understanding. The main obstacle is students' limited initial understanding, but this can be overcome with interactive delivery methods. This program has proven effective in increasing students' awareness of the negative impacts of juvenile delinquency and how to prevent it. It is hoped that similar activities can continue to be developed to form a more responsible young generation.